The Furongian (late Cambrian) trilobite Thailandium’s endemicity reassessed along with a new species of Prosaukia from Ko Tarutao, Thailand - Wernette, Shelly; Hughes, Nigel; Myrow, Paul; Sardsud, Apsorn (Thai Geoscience Journal, 2020)
The trilobite Thailandium solum, the type species of Thailandium, is a large “saukiid” species known only from the Ao Mo Lae Formation of the Tarutao Group, Thailand. In addition to the type species occurrence in Thailand, Thailandium is also reported from northern Henan, China as Thailandium truncatum Zhou and from Australia’s Pacoota Sandstone as an undeterminate species. Type material of Prosaukia misa, the type species of Prosaukia, as well as recent collections of Thailandium solum, Prosaukia tarutaoensis (Kobayashi, 1957), and a new species of Prosaukia, P. oculata, from Ko Tarutao, Thailand are used to reevaluate the generic identity of the Australian and north Chinese material using landmark-based morphometric analysis. The new material of Prosaukia and Thailandium, all from the Ao Mo Lae Formation, reveal that the Australian material is better characterized as Prosaukia. The cranidium of north China’s Thailandium truncatum is geometrically comparable to Thailandium solum, but differs notably in overall relief and in the anterior border structure and proportions. Here we assign it tentatively to another “saukiid” genus. These morphometric and qualitative comparisons facilitate a refined generic diagnosis for Thailandium, resulting in its restriction to a monospecific genus.